Effectiveness of Stalevo Drug Usage in Parkinson's Patients: A Narrative Review - M Andri Prasetyo; Fauna Herawati (Postgraduate, University of Mataram, 2026)
Parkinson's Disease (PD) is a neurodegenerative disorder that affects patients' quality of life, with primary motor symptoms such as tremor, muscle rigidity, and bradykinesia. Levodopa is the mainstay of PD therapy, but approximately 80% of patients experience motor complications, such as motor fluctuations and